Operational capabilities’ development: a co-evolutionary perspective - Prim, Alexandre Luis (2018)
If operational capabilities is the reason for competitive advantage of companies and a way for explain performance heterogeneity across them, how do companies develop it? Putting myself in an executive position, undoubtedly I would be eager to find out. Current literature of operational capabilities has addressed limited discussion over that topic. Therefore, this study was motivated from both theoretical and managerial gaps, so, it seeks to analyze the process of operational capability development. Co-evolutionary theory was used to support this study regarding some limitations on theories used by previous studies, such as Evolutionary Theory, Resource-Based Theory, and Microfoundations. Therefore, this study is structured by three chapters: (1) explains the theoretical gap of operational capabilities and proposes a new conceptualization of its development process, as well as indicate some ways for future studies; (2) refers to a quantitative study for analyzing the impact of internal and external mechanisms on the operational capabilities development; (3) consist an inductive qualitative study for revealing ways adopted by four brewery companies regarding the quality capability development.